High Prevalence of Malnutrition and Associated Factors in Newly Diagnosed Upper Gastrointestinal Cancer Patients: A Cross-Sectional Study - Chiou Yi, Ho; Zhen Hong, Ban (Asian Pacific Journal of Cancer Care, 2024)
Introduction: Malnutrition is a common and significant complication in patients with upper gastrointestinal cancers (UGIC), negatively impacting treatment outcomes and prognosis. This study aimed to determine the prevalence of malnutrition and its associated factors in newly diagnosed UGIC patients before treatment. Material and Methods: This cross-sectional study was conducted between October 2020 and March 2022, enrolling newly diagnosed UGIC patients. Data collected included sociodemographics, clinical characteristics (cancer type, stage, comorbidities), functional status (ECOG performance status), anthropometrics (weight, height, weight loss in the past month), biochemical parameters (full blood count, albumin), dietary intake (total daily energy and protein), and malnutrition assessment using the Subjective Global Assessment (SGA). Results: Out of 409 participants, 92.1% were malnourished. The mean age was 60.3 ± 12.5 years, and the mean weight was 57.8 ± 15.1 kg. Significant weight loss (mean -8.2 ± 6.0%) was observed. The majority of patients experienced vomiting (88%) and dysphagia (96%), with 51.3% having an ECOG performance status of 2. Multiple linear regression analysis identified several significant factors associated with malnutrition: percentage of weight loss in the past month, serum albumin levels, dyspepsia, dysphagia, lymphocyte count, and male gender. Conclusion: This study reveals a high prevalence of malnutrition among newly diagnosed UGIC patients, highlighting the need for early identification and intervention. The identified factors associated with malnutrition provide valuable insights for screening and risk assessment. Early nutrition screening, assessment, and timely interventions are crucial for optimizing nutritional status and improving treatment outcomes in this vulnerable patient population.